EFFECT OF DIETARY MODIFICATION AND EXERCISE IN CONTROLLING THE METABOLIC PROFILE AND STRESS ON EMERGENCY MEDICINE DOCTORS AND NURSES (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Doctors and nurses working in emergency departments (EDs) face chronic occupational stress from long working hours, exposure to critical illness, and demanding clinical responsibilities, predisposing them to adverse metabolic outcomes. This study evaluated the effect of a structured dietary modification and exercise intervention on the metabolic profile and perceived stress of ED healthcare professionals.Methods: A quasi-experimental, single-arm, pre-post study was conducted among 37 doctors and nurses (of 40 enrolled) in the Emergency Department of Believers Church Medical College Hospital, Thiruvalla, India, over 61 days. Participants were trained to abstain from refined sugar and processed food, use stairs instead of elevators, perform body-weight strength training, and walk briskly for 10 minutes daily. Weight, body mass index (BMI), random blood sugar (RBS), lipid profile, liver enzymes (SGOT, SGPT), serum cortisol, and Perceived Stress Score (PSS) were recorded at baseline and on day 61. Paired t-test or Wilcoxon signed-rank test was used for pre-post comparisons, and the Mann-Whitney U test for gender- and profession-wise comparisons.Results: Significant reductions were observed in weight (73.08 to 69.08 kg), BMI (27.66 to 26.15 kg/m²), RBS (110.35 to 104.19 mg/dL), LDL, total cholesterol, triglycerides, SGOT, SGPT, serum cortisol (82.59 to 69.32 nmol/L), and PSS (25.59 to 12.05) (all p